Metropolitan and peripheral "Entrepôts" for transitional labour markets - Lars Olof Persson (European Regional Science Association (ERSA), 2002)
Differences in national welfare systems are reflected in rates of labour market participation for different segments of labour across the EU member states. The Nordic countries have of course long stressed 'full employment as a key labour market objective. The public sector is thus actively used to replace non-paid care with formal jobs. Germany and Austria on the other hand, both of which have less developed childcare systems, in practice treat males as the primary household wage earners. Moreover, several Southern member states consider the 'extended family' to have responsibility for those family members in need, which obviously limits the chances of certain segments of the population from entering or indeed re-entering the regular labour market. However, notwithstanding such differences in emphasis, the notion of 'full employment' eventually found its way onto the agenda of the European Union. The member states were moreover unanimous in their belief that this goal would require significant levels of investment in the areas of employment and social policy. The notion of the activation of all segments of labour is accentuated: e.g. the goal requires at least 50 per cent of people aged over 55 years in the EU to be employed in 2010. A new sub-goal was also set for the employment rate of women, at 10 percentage points below the male/female average. Common standards are also to be established which will enable EU wide comparisons of access to childcare and to care of the elderly. The differences in employment frequencies between EU member states remain large, but on the whole they now seem to be converging. On the other hand, regional differences within member states are reported to be on the increase. As such, the transitional characteristics of the labour market are becoming more transparent: Each transition or career - such as from education to work, from care to work, or from unemployment to work, etc - can be temporary and repetitious. Transitions can now of course occur at almost any time of one's 'working life'. There are theories explaining the nature and scope of such 'transitional' behaviour exhibited by the current labour force, stressing, among other things, the individual choice of life-style, life chances or career options in different places. The other side of the coin of course is that rapid economic restructuring increases the risk for non-voluntary changes in employment status. The regions within member states thus perform as more or less efficient 'entrepôts' for transitional labour markets, depending primarily on diversity and the vitality of its industrial structure and on the demographic structure of the labour force. In general, labour markets in Metropolitan regions are expected to permit higher rates of transition, reflecting more individual freedom of choice, than do small and less diverse LLMs. However, performance is inevitably moderated by the welfare system prevalent in each country. In all probability then it is the countries that have an 'individual' rather than a 'household' focus on labour market participation that will be better prepared for high rates of transition. The purpose of this paper is thus to outline a typology of local labour markets across Europe, reflecting the current range of variation in economic and geographic structures as well as in social policy, and to- discuss feasible mixes of policy measures to help achieve the common European goal of full employment, and to help facilitate transition in all types of regions.
Keywords: 330